THE NEHRU PHENOMENON: THE CORNERSTONE OF NATIONAL LIBERATION AND MODERN INDIA - Primov Mukhiddinjon Omonovich; Asatillayeva Munisa Shuxrat qizi (Western European Studies, 2025)
This article highlights the life, political activity, and personal qualities of Jawaharlal Nehru, a great political figure who played an important role in the struggle for India's independence and left a deep mark on the country's history. Nehru's participation in the national liberation movement, his role in the Indian National Congress, his struggle against British colonialism, his position in the field of international relations, his humanistic views, and loyalty to the principles of social justice are analyzed. His personal life, family, and connections with Gandhi and other prominent figures are also examined. The article also analyzes Nehru's visit to Uzbekistan, in particular to Samarkand, and his high assessment of the historical and cultural heritage. His thoughts about the Baburids in the work "The Way of Life in India" and his respect for the scientific heritage of Abu Rayhan Beruni are cited as a historical source
Keywords: Jawaharlal Nehru; Indian National Congress; independence movement